Geographical variation in the diet of the Antarctic fur seal Arctocephalus gazella - Casaux, Ricardo Jorge; Baroni, Paola Andrea; Arrighetti, Florencia; Ramon, Analia Ines; Carlini, Alejandro (Polar Biology)
The diet of non-breeding male Antarctic fur seals Arctocephalus gazella was investigated at different localities of the Antarctic Peninsula (Cierva Point and Hope Bay), South Shetland Islands (Deception Island and Potter Peninsula) and the South Orkney Islands (Laurie Island), by the analysis of 438 scats collected from January to March 2000. The composition of the diet was diverse, with both pelagic and benthic-demersal prey represented in the samples. Antarctic krill Euphausia superba was the most frequent and numerous prey at all the study sites except at Cierva Point, followed by fish, penguins and cephalopods. Antarctic krill also predominated by mass, followed by either fish or penguins. Fish were the second most important prey by mass at the Antarctic Peninsula whereas penguins were the second most important prey by mass at the South Shetland and South Orkney Islands. Among fish, Pleuragramma antarcticum was the most important species in the diet of the Antarctic fur seals at the Antarctic Peninsula whereas Gymnoscopelus nicholsi predominated at the South Shetland and South Orkney Islands. The results are compared with previous studies, and the possibility of implementing monitoring studies on the distribution/abundance of myctophids and P. antarcticum based on the analysis of the diet of the Antarctic fur seal is considered. Fil: Casaux, Ricardo Jorge. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Baroni, Paola Andrea. Universidad de Buenos Aires. Facultad de Farmacia y Bioquímica; Argentina Fil: Arrighetti, Florencia. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Ramon, Analia Ines. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad ...